Pelatihan Keterampilan Kerja untuk Memberdayakan Remaja Putus Sekolah - Losa, Marlina; Mokalu, Anneke; Selfia, Nita (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Adolescence is a productive, creative, and potential age, because teenagers have a strong physique, high enthusiasm, and their abilities can still be developed optimally. In line with the age of adolescence is also a transition period that is very vulnerable and vulnerable to problems as a result of changes that force adjustments to their living conditions. The existence of the problem of teenagers dropping out of school in the community who do not have jobs, can cause new problems that can threaten the peace of society. One of the efforts made by the government to deal with these problems is through social guidance programs and coaching as well as job skills training, including motor mechanic and electronics skills training which is carried out by the Sub Unit of the Social Empowerment House for Youth Development in Bolaang Mongondow Regency for 3 months, which aims to fostering the independence attitude of dropout teenagers, so that they are skilled and have high performance that can improve their quality of life. The results of the training that have been given have an impact on the independence of out-of-school teenagers in opening a business, working, and having self-confidence, responsibility, and being able to interact with the surrounding social environment.